On coordinated control strategies for networked dynamic control systems - an application to AUVs - João Borges de Sousa (2002)
The specification and design of coordinated control strategies for networked vehicles and systems is discussed. A strategy to find the local minimum of an oceanographic scalar field with networked autonomous underwater vehicles (AUV) is presented. The strategy consists in coordinating the motions of the AUVs to implement a modified version of the simplex optimization algorithm. In the original algorithm, the scalar field is given by a function. In the modified version, the scalar field is given by the phenomenon itself. The AUVs sample the phenomenon to calculate the directions of descent, and to minimize the phenomenon along each direction of descent. The strategy is discussed in the more general context of coordination and control of networked vehicles and systems.